Bioalcohol production Biochemical conversion of lignocellulosic biomass - Waldron, K. W. (Woodhead Publishing Online., 2010)
This book covers the process engineering, technology, modelling and integration of the entire production chain, from feedstock pretreatment on to hydrolysis, fermentation, and purification. Primarily reviewing bioethanol production, coverage extends to the production of longer-chain bioalcohols which will be elemental to the future of the industry.